2012
DOI: 10.1681/asn.2012020126
|View full text |Cite
|
Sign up to set email alerts
|

PGD2-CRTH2 Pathway Promotes Tubulointerstitial Fibrosis

Abstract: Urinary excretion of lipocalin-type PGD 2 synthase (L-PGDS), which converts PG H 2 to PGD 2 , increases in early diabetic nephropathy. In addition, L-PGDS expression in the tubular epithelium increases in adriamycin-induced nephropathy, suggesting that locally produced L-PGDS may promote the development of CKD. In this study, we found that L-PGDS-derived PGD 2 contributes to the progression of renal fibrosis via CRTH2-mediated activation of Th2 lymphocytes. In a mouse model, the tubular epithelium synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 38 publications
(40 reference statements)
3
46
1
3
Order By: Relevance
“…In lupusprone mice, STAT6 deficiency or anti-IL-4 Ab treatment ameliorates kidney disease, particularly glomerulosclerosis (53). Additionally, unilateral urethral obstruction induced tubulointerstitial fibrosis, which was ameliorated by knock-out of IL-4 and IL-13 (54). In our microarray data, expression levels of genes implicated in renal diseases, such as collagen VI, IL-6, LTBP1, and SOCS1, were markedly induced by IL-4 ( Table 1), suggesting that IL-4 might play a crucial role in the progression of renal disease.…”
Section: Discussionmentioning
confidence: 76%
“…In lupusprone mice, STAT6 deficiency or anti-IL-4 Ab treatment ameliorates kidney disease, particularly glomerulosclerosis (53). Additionally, unilateral urethral obstruction induced tubulointerstitial fibrosis, which was ameliorated by knock-out of IL-4 and IL-13 (54). In our microarray data, expression levels of genes implicated in renal diseases, such as collagen VI, IL-6, LTBP1, and SOCS1, were markedly induced by IL-4 ( Table 1), suggesting that IL-4 might play a crucial role in the progression of renal disease.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, IL-4 and IL-13 stimulation in human macrophages, which promotes M2 polarization, increases ACE expression while LPS and IFN-γ stimulation, which promotes M1 polarization reduce ACE expression in macrophages [60]. Further, Ito et al elegantly demonstrated that these Th2-associated cytokines (IL-4, IL-13 and PDE2) not only promote the development of M2-macrophages, but also were essential for the fibrotic responses in UUO kidney models in mice [61]. Hence ACE inhibition in vivo may counteract production of Th2/M2 associated cytokines thereby promoting a sustained M1 macrophage population.…”
Section: Discussionmentioning
confidence: 99%
“…ONO-1301 protected UUO kidneys against fibrosis via the induction of HGF, an antifibrotic factor that counteracts TGF-b [25]. In addition, PGD 2 has been suggested to slow the progression of renal fibrosis via CRTH2-mediated activation of Th2 lymphocytes [26].…”
Section: Discussionmentioning
confidence: 99%